The effect of extreme heat on economic growth: Evidence from Latin America - Bridgett Hoffmann; Juliana Due\~nas; Alejandra Goytia (Inter-American Development Bank (IDB), 2024)
Climate change is projected to increase the frequency and intensity of extremely hot days. We use a panel regression framework at the sub-national (i.e., region) level to identify the effect of extreme heat on economic growth in Latin America accounting for acclimation to the season and to the local climate. Extreme heat has a negative and significant impact on economic growth, and the magnitude of the impact is increasing in the intensity and duration of heat. Our results suggest that the impact of each additional consecutive day of extreme heat is greater than the impact of the prior day. Extreme heat affects economic growth directly in addition to its indirect effect through higher seasonal mean temperatures and extreme heat could account for 34-68% of the total projected reduction in the annual economic growth rate at midcentury due to temperature change. Our results suggest that extreme heat is one potential channel for the documented non-linearity in the impacts of rising mean temperature.
Keywords: Q5; Q54; Q51; 330; Extreme heat; Heat waves; Economic growth; Latin America